Gnosticism, church unity and the Nicene Creed - C. F.C. Coetzee (In die Skriflig, 2008)
Gnosticism (derived from the Greek word “gnosis; knowledge”) is the well-known phenomenon or movement which dates from the first centuries of church history. The teaching of Gnosticism questioned and/or contradicted the teaching of the church on some of the fundamental truths of Scripture. Apart from Gnosticism, the Early Church also had to deal with the heresy of Arianism. In the Nicene Creed, formulated by the councils of Nicea (325 AD) and Constantinople (381 AD) the universal or catholic church responded officially to the heresies of both Gnosticism and Arianism. In the final edition of the Nicene Creed we also find an article on the unity, holiness, catholicity and apostolicity of the church. Both Gnosticism and Arianism posed a serious threat to the unity of the church.